Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1002/cncr.22126
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and mortality of cutaneous melanoma in southern Germany

Abstract: BACKGROUND Cutaneous melanoma (CM) incidence and mortality have risen dramatically during the past 2 generations, particularly among Caucasian populations. Detailed, long‐term trends of CM in relation to clinical and pathologic characteristics in a Central European population have not been published to date. METHODS The current study was based on 1980 patients with invasive CM diagnosed in Southern Germany during the years from 1976 to 2003 documented by the Central Malignant Melanoma Registry. The German stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
0
6

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(66 citation statements)
references
References 31 publications
3
57
0
6
Order By: Relevance
“…Malignant melanoma represents one of the most aggressive malignancies with a highly chemoresistant and radioresistant metastatic stage (Flaherty, 2006), offering a poor prognosis for affected patients (Lasithiotakis et al, 2006). Therefore, therapeutic strategies combining chemotherapeutic drugs and tumor selective death ligands are under investigation to improve cancer treatment (Ganten et al, 2006;Zhang et al, 2006;Koschny et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Malignant melanoma represents one of the most aggressive malignancies with a highly chemoresistant and radioresistant metastatic stage (Flaherty, 2006), offering a poor prognosis for affected patients (Lasithiotakis et al, 2006). Therefore, therapeutic strategies combining chemotherapeutic drugs and tumor selective death ligands are under investigation to improve cancer treatment (Ganten et al, 2006;Zhang et al, 2006;Koschny et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Malignant melanoma represents a malignancy with most rapidly increasing incidences offering a poor prognosis for patients with metastatic disease (Lasithiotakis et al, 2006). Melanomas develop and progress in a sequence of defined stages from nevic lesions or normal cells (Meier et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Since the mid-1980s, however, the rates of increase began decreasing or at least leveling off. [4][5][6][7][8][9] Recent studies showed that the observed leveling-off in rates predominantly occurred in younger persons and the patterns showed positive effects for cohorts born after 1945 or 1950.…”
mentioning
confidence: 99%
“…4,6,9 Conversely, the rate of increase in melanoma incidence and mortality has been significantly higher for age groups older than 60 years in Europe, the US, and Australia. [1][2][3][4] Older persons present more frequently with advanced tumors, lentigo malignant melanomas (LMM), and melanomas arising in sun-exposed anatomic areas and the disease-specific survival (DSS) of melanoma patients over 60 years old is significantly shorter compared with younger ages. 10 Thus, age seems to be a significant prognostic factor for melanoma and its prognostic significance has been demonstrated likewise after adjusting for all known prognostic variables such as tumor thickness, ulceration, etc.…”
mentioning
confidence: 99%